Pengelolaan modal kerja guna menjaga likuiditas dan profitabilitas - Asadi Asadi; Ahmad Mukoffi; Risky Aprilia Dwi Susanti (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This research aims to analyze how working capital management maintains liquidity and profitability in SMEs. The data collection method used in this research is documentation. The analysis technique used is the ratio of liquidity and profitability. The findings of this study indicate that SMEs can maintain their liquidity. SMEs are less able to manage working capital to increase profitability.